Initial testing (stage 1) of the histone deacetylase inhibitor, quisinostat (JNJ‐26481585), by the Pediatric Preclinical Testing Program. Issue 2 (4th September 2013) - Carol, Hernan; Gorlick, Richard; Kolb, E. Anders; Morton, Christopher L.; Manesh, Donya Moradi; Keir, Stephen T.; Reynolds, C. Patrick; Kang, Min H.; Maris, John M.; Wozniak, Amy; Hickson, Ian; Lyalin, Dmitry; et al.
Abstract Background Quisinostat (JNJ‐26481585) is a second‐generation pyrimidyl‐hydroxamic acid histone deacetylase (HDAC) inhibitor with high cellular potency towards Class I and II HDACs. Quisinostat was selected for clinical development as it showed prolonged pharmacodynamic effects in vivo and demonstrated improved single agent antitumoral efficacy compared to other analogs. Procedures Quisinostat was tested against the PPTP in vitro panel at concentrations ranging from 1.0 nM to 10 μM and was tested against the PPTP in vivo panels at a dose of 5 mg/kg (solid tumors) or 2.5 mg/kg (ALL models) administered intraperitoneally daily × 21. Results In vitro quisinostat demonstrated potent cytotoxic activity, with T/C% values approaching 0% for all of the cell lines at the highest concentration tested. The median relative IC50 value for the PPTP cell lines was 2.2 nM (range <1–19 nM). quisinostat induced significant differences in EFS distribution compared to control in 21 of 33 (64%) of the evaluable solid tumor xenografts and in 4 of 8 (50%) of the evaluable ALL xenografts. An objective response was observed in 1 of 33 solid tumor xenografts while for the ALL panel, two xenografts achieved complete response (CR) or maintained CR, and a third ALL xenograft achieved stable disease. Conclusions Quisinostat demonstrated broad activity in vitro, and retarded growth in the majority of solid tumor xenografts studied. The most consistent in vivo activity signals observed were for the glioblastoma xenografts and T‐cell ALL xenografts. Pediatr Blood Cancer 2014;61:245–252. © 2013 Wiley Periodicals, Inc.